Dynamical resource allocation models for bioreactor optimization. Issue 19 (2018) - Jeanne, Guillaume; Goelzer, Anne; Tebbani, Sihem; Dumur, Didier; Fromion, Vincent
Abstract: Resource allocation based models were shown to capture the main bacterial cell design principles in steady-state, thus managing the resource allocation between cell processes, and in fine growth rate. This paper introduces the basis of extension of resource allocation models to dynamical conditions. The framework is applied to a bioreactor operating in batch mode for optimizing the production of added-value compounds by bacteria. The optimal predicted strategy is analyzed and discussed in light of the strategies obtained with other types of models. This framework should offer new opportunities for biotechnologies, especially for the simultaneous optimization of strain design and bioprocess control.